Green Accounting, Material Flow Cost, And Environmental Performance as Predictors of Corporate Sustainability - Fransiskus Eduardus DAROMES; Yuri Ono; Kunradus Kampo (Universitas Agung Podomoro, 2023)
The main objective of this study is to analyze the effect of implementing green accounting, material flow cost accounting, and environmental performance on corporate sustainability. This study uses stakeholder theory and legitimacy theory. This study uses secondary data obtained by the documentary method. The data source in this study is the annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The sample selection was carried out using a purposive sampling method and analyzed using multiple regression analysis. The results of the study show that green accounting has a negative and significant effect on corporate sustainability. MFCA (production costs) has a positive and insignificant effect on corporate sustainability. MFCA (land area of production coverage) has a negative and significant effect on corporate sustainability. MFCA (production value) has a positive and significant effect on corporate sustainability. Environmental performance has a positive and significant effect on corporate sustainability.